Design of Experiments Application for Machining Process Analyse - Javorek, Lubomir; Vargovská, Maria (International Journal of Engineering and Management Sciences, 2021)
In this contribution are results from machining of the aluminium alloy by spiral router. The experiment was designed as full 3 - factors and 2-levels process and for evaluation of input factors to output parameters – Fx and Fy components were used Paret´s diagram and Lorentz´s line. The input parameters were: revolution speed (4000/min. and 6000/min.), working engagement of a cutting edge (depth of cut) ae (1 mm and 3 mm), back engagement of a cutting edge (with of cut) ap (5 mm and 15 mm) and down (climb) milling.